Quantum dots labelling allows detection of the homing of mesenchymal stem cells administered as immunomodulatory therapy in an experimental model of pancreatic islets transplantation. Issue 3 (15th November 2016) - Mannucci, Silvia; Calderan, Laura; Quaranta, Paola; Antonini, Sara; Mosca, Franco; Longoni, Biancamaria; Marzola, Pasquina; Boschi, Federico
Abstract: Cell transplantation is considered a promising therapeutic approach in several pathologies but still needs innovative and non‐invasive imaging technologies to be validated. The use of mesenchymal stem cells (MSCs) attracts major interest in clinical transplantation thanks to their regenerative properties, low immunogenicity and ability to regulate immune responses. In several animal models, MSCs are used in co‐transplantation with pancreatic islets (PIs) for the treatment of type I diabetes, supporting graft survival and prolonging normal glycaemia levels. In this study we investigated the homing of systemically administered MSCs in a rat model of pancreatic portal vein transplantation. MSCs labelled with quantum dots (Qdots) were systemically injected by tail vein and monitored by optical fluorescence imaging. The fluorescence signal of the liver in animals co‐transplanted with MSCs and PIs was significantly higher than in control animals in which MSCs alone were transplanted. By using magnetic labelling of PIs, the homing of PIs into liver was independently confirmed. These results demonstrate that MSCs injected in peripheral blood vessels preferentially accumulate into liver when PIs are transplanted in the same organ. Moreover, we prove that bimodal MRI‐fluorescence imaging allows specific monitoring of the fate of two types of cells.